2017
DOI: 10.7860/jcdr/2017/27583.10178
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Metaboreflex on Cardiovascular System in Subjects of Metabolic Syndrome

Abstract: INTRODUCTIONPhysical activity is any bodily movement produced by skeletal muscles that results in energy expenditure [1]. An emphasis has been placed on understanding the role of physical activity in the prevention and management of obesity which is responsible for the increasing prevalence of metabolic syndrome in the U.S. and worldwide due to sedentary lifestyles [2][3][4].When physical activity is planned, structured, and repetitive with an objective to improve or maintain the physical fitness, then it is k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 25 publications
(9 reference statements)
1
4
0
Order By: Relevance
“…Similar effects during exercise are observed regarding the impact of MetS on muscle metaboreflex activation, in which an enhanced vasoconstrictor response is observed similar to what has been seen in hypertension [22,23,53,82]. Furthermore, studies assessing the impact of obesity have shown that obesity alone does not significantly alter hemodynamics [23].…”
Section: Autonomic Function: Hypertensionsupporting
confidence: 59%
See 1 more Smart Citation
“…Similar effects during exercise are observed regarding the impact of MetS on muscle metaboreflex activation, in which an enhanced vasoconstrictor response is observed similar to what has been seen in hypertension [22,23,53,82]. Furthermore, studies assessing the impact of obesity have shown that obesity alone does not significantly alter hemodynamics [23].…”
Section: Autonomic Function: Hypertensionsupporting
confidence: 59%
“…Both hypertension and MetS have been linked to autonomic dysfunction and exercise intolerance, [14][15][16][17][18][19]22,23,32,53]. Hypertension has been studied extensively in the context of exercise; hypertension modifies the muscle metaboreflex and the arterial baroreflex as well as their interactions [15,[17][18][19]32,54,55].…”
Section: Autonomic Function: Hypertensionmentioning
confidence: 99%
“…It has long been known that during acute circulatory stresses, such as exercise, arterial pressure is controlled almost entirely by nervous reflex mechanisms [37]. Moreover, SBP has been reported to be more sensitive to metaboreflex than DBP in individuals with autonomic impairment [38,39]. It is therefore possible that a greater sympathetic outflow resulting from metaboreflex within the short periods of PEMI and CER protocols had more effect on SBP than DBP.…”
Section: Discussionmentioning
confidence: 99%
“…This accumulation triggers the metaboreflex that redirects the blood flow via sympathetic activation from the periphery muscles to the diaphragmatic area, thus avoiding dyspnoea due to reduction in blood supply to respiratory muscles. However, this peripheral blood flow redistribution may be responsible for the interruption of exercise as well as activities of daily living due to peripheral muscle fatigue [9,10]. Therefore, delaying the onset of this reflex might predispose individuals to a more active lifestyle and improved exercise tolerance.…”
Section: Introductionmentioning
confidence: 99%